MENGATASI KEJAHATAN SIBER DALAM HUKUM ISLAM: STRATEGI DAN PENDEKATAN HUKUM - Muhammad Sibawaihi; Devika Rosa Guspita; Badriyah Badriyah (Justicia Islamica, 2024)
This research examines Islamic law strategies in Indonesia to combat cybercrime and illegal data dissemination. The main focus is to identify and analyze relevant Islamic law approaches in cybercrime in Indonesia and assess their effectiveness in addressing illegal data dissemination. Qualitative methodology was used to collect data, including document analysis and expert interviews. The results show that applying Islamic law principles such as justice, transparency, and accountability can strengthen law enforcement policies and practices in addressing cybercrime. The findings also emphasize the importance of improving education and awareness about Islamic law in preventing cybercrime. As a practical contribution, this research offers a legal framework that policymakers and law enforcement can integrate to address cybercrime and illegal data dissemination more effectively. By referring to principles such as justice (al-'adl) and the protection of individual rights (huquq al-insan), the article proposes preventive and enforcement measures that can be applied in the context of legal product formulation, policy drafting and more flexible law enforcement.